In Vitro Recombination of Poliovirus with Coxsackie A Virus Serotype 18 at Downstream Nonstructural Protein-Coding Regions - ANDI UTAMA; HIROYUKI SHIMIZU (Microbiology Indonesia, 2007)
Many genetic recombinations of poliovirus (PV) are to be found in excreted viruses, including viruses from vaccineassociated paralytic poliomyelitis (VAPP) as well as healthy vaccine recipients. Most recombinations were among different serotypes of PVs. However, recombination can also occur between PV and other enteroviruses. It was predicted that the hot spot of the recombination is in the nonstructural protein-coding regions, but the exact site is may be different in each recombination. We have demonstrated that the construct recombinant virus between PV and coxsackie A virus serotype 11 (CAV-11), or with CAV-17 with recombination site in the N-term of 2C-coding region, were viable. However, the recombination of PV with CAV-18 at this site was not viable. To determine if the recombination between PV and CAV-18 can occur at other sites, eight chimeric cDNAs (between PV [isolate PJ156] and CAV-18 [PJ156/CAV-18]), all having different recombination sites (2C-8, 2C-133, 2C-235, 2C-268, 2C-287, 2C-327, 3A-67, 3C-60) were constructed using the long-PCR method. The cDNA was then transcribed in vitro and then transfected into the HEp-2 cell-line. As expected, the recombinant virus PJ156/CAV-18, with recombination sites 2C-327, 3A-67, and 3C-60 were viable, while all the others were not. The recombinant viruses displayed a slightly smaller plaque size, but emonstrated quite similar growth as compared to the parental control PJ156. Since analysis for similarity has shown that the homology between PV and CAV-18 was high around these regions, these results supported the copy-choice mechanism of enterovirus recombination.